Artificial mirtron-mediated gene knockdown: functional DMPK silencing in mammalian cells. - Seow, Y; Sibley, C; Wood, M (2012)
Mirtrons are introns that form pre-miRNA hairpins after splicing to produce RNA interference (RNAi) effectors distinct from Drosha-dependent intronic miRNAs. Here we present a design algorithm for artificial mirtrons and demonstrate, for the first time, efficient gene knockdown of myotonic dystrophy protein kinase (DMPK) target sequences in Renilla luciferase 3' UTR and subsequently pathogenic DMPK mRNA, causative of Type I myotonic dystrophy, using artificial mirtrons cloned as eGFP introns. Deep sequencing of artificial mirtrons suggests that functional mature transcripts corresponding to the designed sequence were produced in high abundance. They were further shown to be splicing-dependent, Drosha-independent, and partially dependent on exportin-5, resulting in the precise generation of pre-miRNAs. In a murine myoblast line containing a pathogenic copy of human DMPK with more than 500 CUG repeats, the DMPK artificial mirtron corrected DM1-associated splicing abnormalities of the Serca-1 mRNA, demonstrating the therapeutic potential of mirtron-mediated RNAi. Thus, further development and exploitation of the unique properties of mirtrons will benefit future research and therapeutic RNAi applications as an alternative to conventional RNAi strategies.